2012
DOI: 10.1097/acm.0b013e31826d7189
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Representation of Women and Minorities in Biomedical Careers

Abstract: The authors have demonstrated that all groups do not benefit equally from diversity initiatives and that competition across related fields can confound efforts to increase diversity in medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Increasing faculty diversity in academic science departments has been a long-standing challenge and has received renewed attention in recent years (Ginther et al, 2016; Ginther et al, 2011; Griffin, 2016; Duehren and Muluk, 2016; Myers et al, 2012). Here, we used data from medical school basic science departments to highlight the impact of potential intervention strategies on the diversity of assistant professors.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing faculty diversity in academic science departments has been a long-standing challenge and has received renewed attention in recent years (Ginther et al, 2016; Ginther et al, 2011; Griffin, 2016; Duehren and Muluk, 2016; Myers et al, 2012). Here, we used data from medical school basic science departments to highlight the impact of potential intervention strategies on the diversity of assistant professors.…”
Section: Discussionmentioning
confidence: 99%
“…9 When a subgroup’s representation ratio is greater than one, they exhibit greater representation in that educational or career stage compared to the previous stage or relevant labor market in terms of NIH-funded paths. When the ratio is less than one, the subgroup is underrepresented; when the ratio is equal to one, the representation of the subgroup among recipients of the next stage is equal to the subgroup’s representation in the relevant labor market.…”
Section: Methodsmentioning
confidence: 99%
“…Pohlhaus et al 12 and Ginther et al 13,14 found disparities in the NIH research award funding system by sex, race, and ethnicity, and an earlier study by Ginther et al also found that underrepresented racial and ethnic groups fall out of the biomedical educational pathway well before they reach the eligible NIH principal investigator (PI) pool. 15 Myers and Husbands-Fealing 9 examined representation of subgroups within biomedicine and found that not all groups benefit from broad diversity policies in the same way. These studies provide a larger context for understanding diversity within the biomedical workforce.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, there is significant evidence that students from these groups continue to face challenges within the classroom and training environments (Gibbs and Griffin, 2013; Eddy et al ., 2014; Grunspan et al ., 2016; Lauer et al ., 2016). Women and scientists from URM backgrounds remain underrepresented as principal investigators on research grants, as faculty members, and in senior leadership positions (Myers and Fealing, 2012; National Institutes of Health, 2012; Heggeness et al ., 2016; Plank-Bazinet et al ., 2016). Other groups, such as Asian-American scientists, are often well represented in undergraduate and graduate programs and in junior faculty positions (though there are differences across ethnicity), yet still experience stereotyping and remain underrepresented in senior leadership positions (Maramba et al ., 2014).…”
mentioning
confidence: 99%